Brill's companion to Sophocles - Markantonatos, Andreas. (Brill's Companions to Classical Studies., 2012)
Brill's Companion to Sophocles offers 32 specially commissioned essays from leading international scholars which give critical examinations of the progress and direction of numerous wide-ranging debates about various aspects of Sophoclean drama. Each chapter offers an authoritative and state-of-the-art survey of current thinking and research in a particular subject area, as well as covering a wide variety of thematic angles. Recent advances in scholarship have raised new questions about Sophocles and Greek tragedy, and have overturned some long-standing assumptions. Besides presenting a comprehensive and authoritative guide to understanding Sophocles, this companion provides scholars and students with compelling fresh perspectives upon a broad range of issues in the field of Sophoclean studies.